2017
DOI: 10.1002/lpor.201770031
|View full text |Cite
|
Sign up to set email alerts
|

Modifying magnetic dipole spontaneous emission with nanophotonic structures (Laser Photonics Rev. 11(3)/2017)

Abstract: Spontaneous emission of light from materials is typically associated with electric dipole transitions. However, nanoscale emitters with strong magnetic dipole transitions also exist in nature, and they have been intensively studied in recent years. Similarly to electric dipole transitions, the spontaneous decay rate of magnetic dipole emitters can be controlled led by properly engineering the local density of optical states. This paper reviews the recent progress in enhancing magnetic dipole spontaneous emissi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Recently, a series of experimental studies have demonstrated the detection and manipulation of magnetic dipole transitions in lanthanide ions by means of metallic and dielectric interfaces in the visible range and by plasmonic cavities in the near-infrared . In addition, in the past few years, theoretical studies have predicted the extraordinary properties of a certain class of photonic nanostructures, in particular low-loss dielectric resonators and plasmonic nanoantennas, to strongly enhance the optical magnetic field together with the spontaneous emission of magnetic dipoles, ,,,,,,, making them ideal to open new avenues in the emerging field of magneto-nanophotonics. Although several interesting studies have aimed at detecting and studying the magnetic component of light, no experimental demonstration of the manipulation of magnetic spontaneous emission by means of nanoantennas has been reported so far at visible wavelengths.…”
mentioning
confidence: 99%
“…Recently, a series of experimental studies have demonstrated the detection and manipulation of magnetic dipole transitions in lanthanide ions by means of metallic and dielectric interfaces in the visible range and by plasmonic cavities in the near-infrared . In addition, in the past few years, theoretical studies have predicted the extraordinary properties of a certain class of photonic nanostructures, in particular low-loss dielectric resonators and plasmonic nanoantennas, to strongly enhance the optical magnetic field together with the spontaneous emission of magnetic dipoles, ,,,,,,, making them ideal to open new avenues in the emerging field of magneto-nanophotonics. Although several interesting studies have aimed at detecting and studying the magnetic component of light, no experimental demonstration of the manipulation of magnetic spontaneous emission by means of nanoantennas has been reported so far at visible wavelengths.…”
mentioning
confidence: 99%
“…It is worth noting that Mie‐resonant nanostructures can be used for the emission rate enhancement of integrated nanoemitters due to changing the local density of optical states [ 7,11 ] and can be considered as elements of radiative (active) dielectric nanophotonics. [ 12–15 ] Experimentally, nanoscale sources emission enhancement is demonstrated in the visible wavelength range for color centers in nanodiamonds, [ 16,17 ] perovskites, [ 18 ] MoS 2 monolayer, [ 19 ] and europium ions. [ 20 ] Thus, silicon potentially applied as a host matrix for an emitter can be used as a building block of radiative optical elements based on Mie‐resonant nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…Receiving more attention have been interactions produced by coupling electric dipole transitions with the electromagnetic field since the magnetic dipole emission is usually orders of magnitude weaker in most materials. [ 19 ] However, the low losses and high magnetic resonance in the visible range in Si nanoantennas permit reaching a high local density of magnetic states, making the coupling with the magnetic dipolar mode significant. [ 7,13,20 ] This enhanced magnetic field allows the modification of magnetic transitions in some transition metals, such as Cr 3+ , [ 21 ] and lanthanide series ions, like Eu 3+[ 18 ] and Er 3+ , [ 22 ] in which electric dipolar first‐order transitions are normally forbidden.…”
Section: Introductionmentioning
confidence: 99%